RENDERING SUNDANESE CULTURAL TERMS IN ENGLISH - Halimah Halimah; Ida Nuraida; Dinni Nurfajrin Ningsih; Siti Handayani; Deden Nasihin (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT The provision of bilingual tourism information continues to increase. However, the translation of local cultural terms in non-literary tourism texts still faces challenges related to meaning equivalence and limited empirical research, particularly in the context of Sundanese culture. Sundanese cultural terms embody values, social practices, and local identities that do not always have direct equivalents in English. This situation requires translation strategies that can bridge linguistic and cultural differences without erasing the distinctive characteristics of the source culture. This study aims to identify the categories of Sundanese cultural terms in non-literary tourism texts and analyze the strategies used to translate them into English. The study employed a descriptive qualitative design using 20 bilingual tourism documents, including brochures, official tourism websites, and cultural information portals. Data were collected through document analysis by identifying Sundanese cultural terms and their English equivalents. The data were then classified according to Newmark’s cultural categories and analyzed using Molina and Albir’s taxonomy of translation strategies. The findings revealed that organizations, customs, and cultural activities constituted the most dominant category. Description, borrowing, and established equivalent were the most frequently used strategies. The predominance of these strategies reflects translators’ efforts to balance the preservation of Sundanese cultural identity with the need to explain local concepts to international readers. No single strategy was suitable for all cultural terms because each category carried different cultural meanings and levels of translatability. This study provides empirical evidence on the translation of Sundanese cultural terms in non-literary tourism texts and offers a practical reference for developing bilingual tourism content that is communicative, accessible, and sensitive to local culture. ABSTRAK Penyediaan informasi pariwisata dwibahasa terus meningkat, namun penerjemahan istilah budaya lokal dalam teks pariwisata non-sastra masih menghadapi tantangan kesepadanan makna dan keterbatasan kajian empiris, khususnya untuk budaya Sunda. Istilah-istilah budaya Sunda memuat nilai, praktik sosial, dan identitas lokal yang tidak selalu memiliki padanan langsung dalam bahasa Inggris. Situasi ini menuntut strategi penerjemahan yang mampu menjembatani perbedaan bahasa dan budaya tanpa menghapuskan ciri khas sumber budaya. Penelitian ini bertujuan mengidentifikasi kategori istilah budaya Sunda dalam teks pariwisata non-sastra dan menganalisis strategi yang digunakan untuk menerjemahkannya ke bahasa Inggris. Desain penelitian bersifat kualitatif deskriptif dengan sumber data 20 dokumen pariwisata dwibahasa, meliputi brosur, situs web resmi pariwisata, dan portal informasi budaya. Data dikumpulkan melalui analisis dokumen dengan mengidentifikasi istilah budaya Sunda dan padanan bahasa Inggrisnya. Selanjutnya data diklasifikasikan menurut kategori budaya Newmark dan dianalisis menggunakan taksonomi strategi penerjemahan Molina dan Albir. Hasil menunjukkan bahwa organisasi, adat istiadat, dan aktivitas budaya adalah kategori paling dominan. Strategi yang paling sering digunakan adalah description, borrowing, dan established equivalent. Dominasi strategi tersebut menggambarkan upaya penerjemah menyeimbangkan pemertahanan identitas budaya Sunda dan kebutuhan menjelaskan konsep lokal bagi pembaca internasional. Tidak ada satu strategi tunggal yang cocok untuk semua istilah, karena setiap kategori membawa muatan budaya dan tingkat keterjemahan yang berbeda. Penelitian ini memberikan bukti empiris tentang penerjemahan istilah budaya Sunda dalam teks pariwisata non-sastra dan dapat menjadi acuan praktis bagi penyusunan konten pariwisata dwibahasa yang komunikatif, mudah dipahami, dan sensitif terhadap budaya lokal.